Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae) - Sánchez-Nivicela, Juan C.; Peloso, Pedro L. V.; Urgiles, Verónica L.; Yánez-Muñoz, Mario H.; Sagredo, Yerka; Páez, Nadia; Ron, Santiago (Zootaxa, 2020)
Elachistocleis is a Neotropical genus of microhylid frogs with 18 species, most of which occur east of the Andes in South America. Here, we present a new phylogeny of Gastrophryninae and describe and name a new species of Elachistocleis from southern Ecuador—the first to be found west of the Andes and also the first from Ecuador. Our phylogeny is based on DNA sequences of the mitochondrial genes 12S rRNA, 16S rRNA, COI, and the nuclear genes BDNF, cmyc2, H3A, 28S, SIA1, and Tyr. Elachistocleis araios sp. n., is the sister species of all other Elachistocleis. The finding of this taxon highlights the probability of the existence of more Elachistocleis species west of the Andes.